Wetland–agriculture interactions: sustaining intergenerational ecosystem services - Dinesh K Marothia (Agricultural Economics Research Review, 2023)
When I received the letter from the President of the Agricultural Economics Research Association (AERA), India, Dr P K Joshi, informing me of the decision of the association to elect me to preside over the 29th Annual Conference of the AERA, I was humbled.